Saúde mental após a pandemia de Covid-19 de profissionais da enfermagem que atuaram em serviços de urgência e emergência - Rezende, Gabriela Teixeira de (2024)
Ways of living, human and social relationships, as well as work processes around the world underwent major transformations with the start of the pandemic. Health professionals, who were already suffering from overload and precarious working conditions, had these conditions heightened and emotional reactions of anxiety, anguish, stress and fear became frequent, especially by those directly involved in fighting Covid-19. The literature points out that highly stressful working conditions leave health service professionals in a situation of great vulnerability. Within this group, nursing is the professional category that, recognized, played a leading role in the fight against Covid-19 and represents the largest number of health professionals in institutions. Therefore, it is important to reflect on the mental health of this population and develop support strategies for this team. The aim is to understand the changes that occurred in the work process of nursing professionals who worked in urgent and emergency services during the fight against the Covid-19 pandemic and how they analyze the effects they suffered on their mental health during the period of health crisis. and at the present time. This is a qualitative, descriptive and exploratory study, theoretically referenced by Work-Related Mental Health, a subfield of Occupational Health, an interdisciplinary perspective whose object is work and its relationships with health processes, illness and mental suffering, which seeks to understand the relationship between these processes and their determinants, arising from objective factors shaped in work situations. We interviewed 7 nursing professionals, aged 26 to 45, who work in the municipal urgency and emergency network in the city of Uberlândia-MG on the front line of fighting Covid-19. The interviews were analyzed using Content Analysis and gave rise to categories such as: 1) Conditions and organization of nursing work; 2) Changes in the nursing work process during the fight against the Covid-19 pandemic; 3) Effects of the pandemic on the mental health of nursing professionals; 4) Strategies developed to deal with 11 the effects on mental health and 5) Repercussions on work and life today. The results point to repercussions on the physical and mental health of nurses today, as well as on their personal and professional lives, through changes in labor relations and repercussions at the institutional level, which must also be evaluated by the contracting institution in order to provide institutional measures of support for professionals.